Relationship stability: Evidence from labor and marriage markets - Iris Kesternich; Bettina Siflinger; James P. Smith; Franziska Valder (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
Behavior in labor and marriage markets follows similar structures when it comes to commitment to long-term relationships. We argue that there is a joint social skill driving stability in both markets. Applying a grouped fixed-effect estimator on data from the Survey of Health, Ageing and Retirement in Europe, we identify types of individuals at risk of instability in both domains. We provide evidence on how economic preferences and personality are related to instability in both markets. We also show negative consequences of instability in terms of reduced life satisfaction and wealth late in life.
Keywords: J12; J24; J63; I31; C33; 330; Relationship Stability; Marriage dissolution; Job turnover; Social Skills; Non-Cognitive Skills; Grouped Fixed-Effect Estimator; Survey of Health; Ageing and Retirement in Europe